2020
DOI: 10.21608/asnj.2021.53261.1092
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Status After Implementing Chest Physiotherapy for Extubated Cardiothoracic Surgery Patients

Abstract: Chest physiotherapy considered basic nursing interventions for patients undergoing cardiothoracic surgery to improve breathing efficiency, oxygenation and pulmonary functions. Aim of the study: to evaluate the pulmonary function status after implementing chest physiotherapy for extubated cardiothoracic surgery patients. Design: Quasi experimental research design (study and control) was used in this study. Setting: cardiothoracic intensive care unit and cardiothoracic department at cardiothoracic hospital that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For instance, a study carried out in Egypt demonstrated that implementation of chest physiotherapy resulted in a notable improvement in pulmonary function and a reduced occurrence of respiratory complications among critically ill patients. 4 Similarly, previous studies reported a positive association between chest physiotherapy and improved oxygenation, reduced hospitalization duration and decreased mortality in critically ill patients. 17 20 Therefore, investigating the effect of immediate chest physiotherapy on pulmonary function among extubated patients in critical care units is crucial in improving patient outcomes.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…For instance, a study carried out in Egypt demonstrated that implementation of chest physiotherapy resulted in a notable improvement in pulmonary function and a reduced occurrence of respiratory complications among critically ill patients. 4 Similarly, previous studies reported a positive association between chest physiotherapy and improved oxygenation, reduced hospitalization duration and decreased mortality in critically ill patients. 17 20 Therefore, investigating the effect of immediate chest physiotherapy on pulmonary function among extubated patients in critical care units is crucial in improving patient outcomes.…”
Section: Introductionmentioning
confidence: 77%
“…1 Studies have also found that ICPT can lower the incidence of pneumonia and lead to a shorter stay in the intensive care unit (ICU). [2][3][4][5] It is important to prevent extubation failure following a critical illness, as reintubation is associated with worse outcomes, longer hospitalization and higher rates of tracheotomies. 6,7 Severe deterioration, prolonged immobility and long-term mechanical ventilation are major risk factors for respiratory complications and muscle weakness in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation